Transforming corporate headquarters: A case study of a collaborative journey - Stephanie Chasserio; Sophie Botte (Journal of Organization Design, 2020)
Transforming the organizational structure of a headquarters in order to decentralize authority and decrease its size remains a huge challenge for international corporations looking for agility. One of the main issues is how to overcome the inertia of corporate headquarters (CHQ). This paper examines a CHQ transformation at an industrial multinational that has developed its own participative method with strong reliance on internal resources and an intensive pace of change. It outlines how internal change agents orchestrate and implement this change at the level of CHQ-but not without some tradeoffs. While the approach adopted has helped CHQ and the organization to develop news skills and ways of working, at the same time some tradeoffs-such as the pace of change and the exclusion of managers from the consultative process-may have had effects on the implementation of change.
Keywords: 650; Change processes; Internal change agents; Corporate headquarters (CHQ)transformation; Collaborative practices